2022
DOI: 10.21315/mjms2022.29.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Regional Medical Tourism Demand in Malaysia: A Qualitative Study of Indonesian Medical Tourists’ Rationale and Preferences

Abstract: Background: This study aims to explore the Indonesian tourists’ demand for medical tourism services in Malaysia. The study also investigates the Indonesian medical tourists’ profiles and their preference for Malaysia for medical treatment services. Methods: This study conducted interviews with 49 potential patients from Indonesia who received cardiac treatment at the National Heart Institute (IJN) in Kuala Lumpur, Malaysia. Results: The findings indicate that the key motives of Indonesian tourists travelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…22 articles were published in English [ 20 22 , 35 38 , 44 – 54 , 58 ], and 3 articles were published in Indonesian language [ 55 – 57 ]. Most participants were from middle to upper class background [ 20 , 21 , 35 , 37 , 38 , 44 , 47 , 54 , 58 , 61 ]. Participants from low economic status were reported in two studies [ 45 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…22 articles were published in English [ 20 22 , 35 38 , 44 – 54 , 58 ], and 3 articles were published in Indonesian language [ 55 – 57 ]. Most participants were from middle to upper class background [ 20 , 21 , 35 , 37 , 38 , 44 , 47 , 54 , 58 , 61 ]. Participants from low economic status were reported in two studies [ 45 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…An overview of the characteristics of the included studies can be found in table 2. Of the 25 articles discussed in the review, 10 studies used qualitative methods [30][31][32][39][40][41][42][43][44][45], 12 studies used quantitative methods [33,[46][47][48][49][50][51][52][53][54][55][56]. Additionally, a mixed-method study [57] articles were published in English [30-33, 39-52, 56], and 3 articles were published in Indonesian language [53][54][55].…”
Section: Results Characteristics Of Included Studiesmentioning
confidence: 99%
“…Such positive attitudes and behaviours of medical staff are re ected in being cheerful, and smiling while serving, and good communication with patients and their families, which also lead to positive patient-doctor relations [59]. Thus, studies with Indonesian patients accessing medical treatment in these countries suggested patients felt their dignity being maintained and respected and no frustration due to feeling unimportant or ignored [42].…”
Section: Person-centred Carementioning
confidence: 99%
“…When developing its medical tourism sector, Malaysia, an ASEAN member, transformed its health services by merging public and private providers. This policy gives the government primary, secondary and personal health services to provide tertiary healthcare ( 31 ). Thus, Malaysia’s private and public services are prepared to enhance existing healthcare facilities in the country’s medical tourism industry, which welcomes the highest proportion of Indonesian patients ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Malaysia, the government chose to attract medical tourists from Indonesia. Individual needs, evaluation services, medical facility services, the presence of relatives in the service destinations and the influence of medical service response bias towards treatment programmes are some elements that affect the choice of medical tourism destinations ( 31 ).…”
Section: Discussionmentioning
confidence: 99%